2023
DOI: 10.1177/00333549221148174
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Optimal Placement of Cooling Centers to Serve Populations at High Risk of Extreme Heat Exposure in 81 US Cities

Abstract: Objective: Although extreme heat can impact the health of anyone, certain groups are disproportionately affected. In urban settings, cooling centers are intended to reduce heat exposure by providing air-conditioned spaces to the public. We examined the characteristics of populations living near cooling centers and how well they serve areas with high social vulnerability. Methods: We identified 1402 cooling centers in 81 US cities from publicly available sources and analyzed markers of urban heat and social vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Evidence suggests that cooling centers in many communities across the United States may be less extensive, less intensely focused on the highest-risk populations, and visited less often than the participating facilities of Maricopa County’s Heat Relief Network. 3,4 We agree with Hondula et al 1 that cooling centers can provide many other benefits and services beyond acute relief from extreme heat. Indeed, there is growing interest in creating community resilience hubs, 5–7 which “address gaps in services or resources in certain communities—both during and between disasters such as hurricanes, pandemics, or floods.” 8 Facilitating awareness of and access to large numbers of cool spaces that serve as informal cooling centers may also effectively complement (and be more highly utilized during heat events than) designated cooling centers.…”
Section: To the Editorsupporting
confidence: 64%
“…Evidence suggests that cooling centers in many communities across the United States may be less extensive, less intensely focused on the highest-risk populations, and visited less often than the participating facilities of Maricopa County’s Heat Relief Network. 3,4 We agree with Hondula et al 1 that cooling centers can provide many other benefits and services beyond acute relief from extreme heat. Indeed, there is growing interest in creating community resilience hubs, 5–7 which “address gaps in services or resources in certain communities—both during and between disasters such as hurricanes, pandemics, or floods.” 8 Facilitating awareness of and access to large numbers of cool spaces that serve as informal cooling centers may also effectively complement (and be more highly utilized during heat events than) designated cooling centers.…”
Section: To the Editorsupporting
confidence: 64%
“…A recent Centers for Disease Control and Prevention report ( Widerynski et al, 2017 ) identified barriers to accessing or using cooling centres include, but are not limited to, knowledge of their location, inability to leave home, limited access to transportation, and negative association of cooling centres for strictly vulnerable populations. Nevertheless, more than 50% of the population in 3 major metropolitans in Canada are within a 15-min walk to a defined cooling centre ( Quick et al, 2022 ), and up to 63% of cooling centres in 81 US cities are within a 0.5-mile radius of ones residence ( Adams et al, 2023 ). No data currently exists to describe the prevalence and accessibility of cooling centres in Slovenia.…”
Section: Discussionmentioning
confidence: 99%
“…14 It was referenced by >200 news outlets in discussions about separating autism from profound autism, and it was shared by several large autism-related groups on X (formerly Twitter). 15 Another article, which examined how well cooling centers serve urban areas with high social vulnerability, 16 owes its relatively high Altmetric score (555, as assessed on February 6, 2024) to a heat wave in July 2023. During 2 days, the article was referenced by >60 news outlets in stories related to surviving excessive heat.…”
Section: Impactful Contentmentioning
confidence: 99%
“…During 2 days, the article was referenced by >60 news outlets in stories related to surviving excessive heat. 17 A third article, which examined the association between the incidence of COVID-19 across levels of social vulnerability and the duration of behavioral policy interventions, 18 received an Altmetric score of 202, largely because of a tweet by CDC’s Office of Health Equity that gained traction. 19…”
Section: Impactful Contentmentioning
confidence: 99%